Organizational Boundary Spanning in Institutionalized Environments - Fennell, Mary L.; Alexander, Jeffrey A. (Academy of Management Journal, 1987)
Using an institutional framework, this study tested hypotheses concerning the differences in boundary-spanning strategies between freestanding organizations and organizations that are members of multiorganizational systems. We compared the effects of both environmental variables and organizational characteristics, using data from a nationwide sample of 901 hospitals. Results show that membership in a system increases the likelihood of hospitals using bridging strategies. Further, organizational complexity in boundary spanning mirrors complexity in an institutional environment in a complex, not simply isomorphic, manner.